Knowledge System in Minangkabau Traditional Poetry: Riffaterre's Semiotic Study - Yosi Wulandari; Dini Eka Wijayanti; I Kadek Purnawan; Yeni Apriani; Emil Septia (Universitas PGRI Sumatera Barat, 2024)
Minangkabau traditional poems contain various traditional topics that are important to explore further. This study aims to describe the knowledge system in Minangkabau Traditional Poetry with the Semiotics Riffaterre approach. This type of research is qualitative descriptive, with the subject of the research being Minangkabau traditional poetry. The object of research in this study is that there are material objects and formal objects. The material object is the Minangkabau traditional poem, and the formal object is the significance of cultural values according to the Semiotic view of Riffaterre. The data collection techniques used are listening, reading, and recording techniques. The data analysis technique uses Michael Riffaterre's Semiotic theory. The results of the study show that 28 Minangkabau traditional poems contain a knowledge system as part of the cultural aspects of the Minangkabau people. The knowledge system presented in Minangkabau traditional poems is generally knowledge of Minangkabau customs, namely about ninik mamak, division of territory, to the concept of customs used in daily life. This research has implications for efforts to preserve Minangkabau cultural heritage and can be used for the development of learning materials about the Minangkabau knowledge system and customs in educational institutions.